Animacy and egophoricity: Grammar, ontology and phylogeny - Dahl, O (Lingua, 2008)
Some results of earlier work on animacy by Kari Fraurud and the author are reviewed, demonstrating the close relationship between (i) the role of animacy as a determinant of grammatical rules and the choice between types of referential expressions, and (ii) statistical regularities in discourse. The idea that animacy is an ontological category is developed further. In the final section, the phylogenetic basis of the notions behind animacy and egophoricity is discussed. It is argued that the grammatical animacy hierarchy corresponds to a three-step cognitive scale: the self is the model for other animate individuals, which are in their turn models for inanimate objects when understood as individual ‘things’.